Performance in Real World- and Virtual Reality-Based Spatial Navigation Tasks in Patients With Vestibular Dysfunction. Issue 10 (December 2021) - Biju, Kevin; Wei, Eric X.; Rebello, Elliott; Matthews, Jacob; He, Qiliang; McNamara, Timothy P.; Agrawal, Yuri
Abstract : Objective: This study evaluated whether vestibular dysfunction is associated with reduced spatial navigation performance. Study Design: Cross-sectional study. Setting: Otolaryngology Clinic in the Johns Hopkins Outpatient Center and an analogous virtual reality (VR) environment. Patients: Eligible patients had diagnosis of unilateral or bilateral vestibular loss. Matched healthy controls were recruited at 1:1 ratio. Interventions: The navigation task involved a route-based or place-based strategy in both real world and VR environments. Main Outcome Measures: Navigation performance was measured by distance travelled relative to optimal distance (i.e., path ratio) and the Judgments of Relative Direction (JRD) task, whereby participants had to recall relative angular distances between landmarks. Results: The study sample included 20 patients with vestibular loss (mean age: 61 yrs, SD: 10.2 yrs) and 20 matched controls (mean age: 60 yrs, SD: 10.4 yrs). Patients with vestibular loss travelled significantly greater distance using both route-based (path ratio 1.3 vs. 1.0, p  = 0.02) and place-based (path ratio 2.6 vs. 2.0, p  = 0.03) strategies in the real world. Overall, participants performed worse in virtual reality compared to real world in both path ratio (2.2 vs. 1.7; p  = 0.04) and JRD error (78° vs. 67°; p  < 0.01). Furthermore, while controls exhibited significant positive correlations between real world and VR performance in place-based ( β  = 0.75; p  < 0.001) and JRD tasks ( β  = 0.70; p  < 0.001), patients with vestibular loss exhibited no similar correlations. Conclusions: The vestibular system appears to play a role in navigation ability during both actual and virtual navigation, suggesting a role for static vestibular signals in navigation performance.